Cardiovascular risk in elite Spanish judo athletes - Casals, C.; Escobar-Molina, R.; Barranco-Ruiz, Y.; Franchini, E.; Carratala-Deval, V.; Huertas, J. R. (Archives of Budo, 2016)
Background and Study Aim: Cardiovascular diseases are the first cause of death globally and, although athletes have a longer life expectancy, they are not exempt from these diseases. Thus, the aim of this study was the presence of cardiovascular-risk factors in elite judo athletes amongst weight categories.